ROUNDTABLE - BUILDING THE TEAM: RULES, ROLES AND RESPONSIBILITIES - Finch, Chris; Pongó, Marcel; Rovira, Mar (Sport- és Egészségtudományi füzetek, 2025)
When it comes to building a team it is the general manager and his subordinates who has the final decision of recruiting players. They conduct scouting, evaluation and take opin-ions from coaching staff and ask for a personality profile from the sport psychologist as well. The talent acquisition process focuses on fit, team culture and individual charac-teristics. Organizational culture determines the criteria for selection and talent identification. The first generation of Rátgéber Academy players were evaluated based on their performance, potential to contribute to the organization and also on family background support . In the recruitment process of the assistant coaches it is important that the candidates must be able to cover blind spots of the head coach, to be easy when around and build good relationships with players.